A Brotherhood Perspective: How African American Male Relationships May Improve Trust and Utilization of Health Care. (November 2013) - Grande, Stuart W.; Sherman, Ledric; Shaw-Ridley, Mary
The objective of this research was to explore interview data to understand and characterize the nature of brotherhood in a sample of African American men at two historically Black colleges and universities. The authors used thematic analysis on semistructured interview data, collected by an ethnically diverse research team. Recruitment and interviews were conducted at two historically Black colleges and universities in Texas. Twenty African American men, 18 to 35 years old, were randomly selected from 62 recruited participants. Five categories framed brotherhood and health care utilization: (a) trust lessens individual barriers to action, (b) identity unites men through a process of authentication, (c) generations lead by example, (d) approaching life as a shared learning experience, and (e) social pressure and ridicule uphold collective action. Findings suggest that participants trust a group view, identify with the collective, and respond to social pressure to conform; therefore, brotherhood acts as a support mechanism, and its validation influences individual-level engagement and nonengagement.